PERAN ADVOKAT TERHADAP PENEGAKAN HUKUM DI PENGADILAN AGAMA - Rosdalina, Rosdalina (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2015)
Advocate is a very noble profession (nobile officium). Noble profession given to these advocates incorporate advocates as one of the chess dynasty law enforcement in Indonesia. Law enforcement conducted by advocates can be done in litigation and non-litigation. The enforcement of this law can be seen first of all as a person or a human element to the quality, qualifications, and culture of each work. In that sense the issue of the rule of law depends on the actor, actors, officials or law enforcement officers themselves. Second, law enforcement can also be seen as an institution, agency or organization with the quality of their own bureaucracy. In this regard we look from the perspective of law enforcement institutions in fact, has not been institutionalized in a rational and impersonal (institutionalized). Advocates have a very important role in terms of law enforcement in the Religious. Religious Court has a number of components absolute competence cases which would require the role of advocate and support services to assist the parties litigating in the Religious. Services rendered by lawyers to their clients is assisting litigation, among others, into power, and give advise.